MEETING POINT OF WAHDAT AL-ADYAN AND RELIGIOUS PLURALISM (A Study on the Thought of Ibn 'Arabi and John Hick) - Ahmad Nurcholis; Muhammad Ngizzul Muttaqin; Heri Efendi (Zawiyah: Jurnal Pemikiran Islam, 2021)
Wahdat al-Adyan promoted by a Sufi figure Ibn ‘Arabi is always associated with religious pluralism developed by Christian religious figure John Hick. The recent understanding of religious pluralism has been assumed to take the legitimacy from Wahdat al-Adyan concept. So it can be understood that the understanding of religious pluralism is a legacy of the Islamic intellectual tradition and teachings. Historically, the concept of Wahdat al-Adyan developed by Ibn ’Arabi then became Wahdat al-Wujud. This concept shows that the concept of God is absolute, while the other is just relative. This is library research. It discusses the concept of Wahdat al-Adyan by Ibn ‘Arabi’s and religious pluralism by John Hick. The purpose of this research is to uncover the meeting point and relationship of Wahdat al-Adyan and religious pluralism. The research findings show that these two concepts have very significant differences in their sources and implications of thought, it indicates that Wahdat al-Adyan and religious pluralism do not have the same rationale.